Effects of the Pelotas (Brazil) Peace Pact on violence and crime: a synthetic control analysisResearch in context - Michelle Degli Esposti; Carolina V.N. Coll; Eduardo Viegas da Silva; Doriam Borges; Emiliano Rojido; Alisson Gomes dos Santos; Ignacio Cano; Joseph Murray (Elsevier, 2023)
Summary: Background: City-led interventions are increasingly advocated to achieve the UN's Sustainable Development Goal to reduce violence for all. We used a new quantitative evaluation method to examine whether a flagship programme, called the "Pelotas Pact for Peace" (the Pacto), has been effective in reducing violence and crime in the city of Pelotas, Brazil. Methods: We used synthetic control methodology to assess the effects of the Pacto from August 2017 to December 2021, and separately before and during the COVID-19 pandemic. Outcomes included monthly rates of homicide and property crime, and yearly rates of assault against women and school drop-out. We constructed synthetic controls (counterfactuals) based on weighted averages from a donor pool of municipalities in Rio Grande do Sul. Weights were identified using pre-intervention outcome trends and confounders (sociodemographics, economics, education, health and development, and drug trafficking). Findings: The Pacto led to an overall 9% reduction in homicide and 7% reduction in robbery in Pelotas. These effects were not uniform across the full post-intervention period as clear effects were only seen during the pandemic period. A 38% reduction in homicide was also specifically associated with the criminal justice strategy of Focussed Deterrence. No significant effects were found for non-violent property crimes, violence against women, and school dropout, irrespective of the post-intervention period. Interpretation: City-level interventions that combine public health and criminal justice approaches could be effective in tackling violence in Brazil. Continued monitoring and evaluation efforts are increasingly needed as cities are proposed as key opportunities for reducing violence for all. Funding: This research was funded by the Wellcome Trust [grant number: 210735_Z_18_Z].